2008
DOI: 10.1007/s00441-008-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the three-dimensional myoarchitecture of bovine esophageal wall with diffusion spectrum imaging and tractography

Abstract: In order to determine the three-dimensional (3D) resolved muscular anatomy of the mammalian esophagus, we have examined its myoarchitecture with diffusion spectrum magnetic resonance imaging (DSI) and tractography. DSI measures diffusion displacement as a function of magnetic gradients of varied direction and intensity and displays the displacement profile as a 3D contour per voxel. In tractography, the orientation vectors of maximum diffusion/voxel are identified, and intervoxel associations are constructed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
(22 reference statements)
2
24
0
Order By: Relevance
“…Furthermore, through this technique, we demonstrate, to our knowledge, two novel structures in the mouse tongue, the looplike muscles located in the superior and inferior regions of the anterior tongue, approximately analogous to the superior and inferior longitudinalis in humans. The presence of complex fiber geometries, such as merging, crossing, or helicity contribute substantially to the function of various other muscular hydrostats, such as the heart (14,17) and the esophagus (14,16,17), and numerous Animalia appendages, such as the elephant trunk (25,26,54) or octopus tentacles (55,56). Acknowledging the influences of multidirectional contractions, the understanding of muscular architecture may support continuum models of force generation in the setting of such hydrostats.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, through this technique, we demonstrate, to our knowledge, two novel structures in the mouse tongue, the looplike muscles located in the superior and inferior regions of the anterior tongue, approximately analogous to the superior and inferior longitudinalis in humans. The presence of complex fiber geometries, such as merging, crossing, or helicity contribute substantially to the function of various other muscular hydrostats, such as the heart (14,17) and the esophagus (14,16,17), and numerous Animalia appendages, such as the elephant trunk (25,26,54) or octopus tentacles (55,56). Acknowledging the influences of multidirectional contractions, the understanding of muscular architecture may support continuum models of force generation in the setting of such hydrostats.…”
Section: Discussionmentioning
confidence: 98%
“…Angular separation so defined forms the underlying construct of the myofiber tract (mesoscale) obtained during streamlining, linking PDF diffusional maxima from one voxel to neighboring voxels. Tract coherence is, in turn, dependent upon voxel-scale angular resolution and the allowable tract generation angle, and has been validated through histological comparison (16,17,39) and microscopic correlation (14,38).…”
Section: Multiscale Geometric Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such tissues include the tongue, 1,2 heart, 3 vasculature, 4 and gastrointestinal tract. 5 We have previously demonstrated the feasibility of imaging 3-D myoarchitecture in whole tissues through the use of diffusion spectrum magnetic resonance imaging ͑DSI͒, 6,7 a method that resolves the orientation of complex multifiber arrays by the identification of one or multiple diffusion maxima per voxel. These diffusion maxima may also be associated into mesoscale constructs ͑myofiber tracts͒ defined by the angular similarity exhibited by the principal diffusion vectors in multiple adjacent voxels.…”
Section: Introductionmentioning
confidence: 99%
“…However, Miller and colleagues (3,16) showed that CM contraction also contributes to axial esophageal shortening because of the spiral morphology of CM in the distal esophagus. Gilbert et al (4) used diffusion tensor imaging and fiber tracking to show that CM fibers are arranged in spiral rather than circular fashion. Spiral angle of the CM increases from the proximal to distal esophagus.…”
mentioning
confidence: 99%